An evaluation of the effects of Ramadan fasting on anthropometric, metabolic and endocrine parameters - Akkoca, Muzaffer; Metin, Ziya Erokay; Topaloğlu, Oya; Tokgöz, Serhat; Cihan, Gökhan; Şan, İshak (Progress in Nutrition, 2018)
Objective: The aim of this study was to examine the effects of the energy and nutrients intake at Ramadan fasting on anthropometric measurements, metabolic and endocrine parameters. Methods: This prospective study included a total of 80 healthy volunteers,  aged 19-50 years, who were fasting during the month of Ramadan. Anthropometric measurements, blood samples were taken and nutritional intake was recorded of all participants at 5 days before Ramadan(BR) and on the 27th day at the end of Ramadan (AR). The anthropometric measurements comprised height, weight, body mass index(BMI), hip-waist circumference, body fat ratio and fat mass measurements. From the blood samples, analysis was made of fasting glucose, insulin, total cholesterol, LDL-C, HDL-C and TG. From the records of food intake, energy and nutrients were calculated. The anthropometric measurements, metabolic and endocrine parameters, energy and nutrients BR and AR were compared generally. Results: In the period from BR to AR in the values, a decrease was determined in body weight (77.4±11.0, 76.2±10.7kg, p